2009
DOI: 10.1186/1755-7682-2-19
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lipid parameters in diabetes mellitus – a Nigerian report

Abstract: Background: Diabetes mellitus (DM) is a disorder that is often associated with cardiovascular events and underlying lipid abnormalities. Cardiovascular complications are common causes of DM deaths in Nigeria yet dyslipidaemia is one aspect of DM that is underdiagnosed and undertreated in our patients. This report seeks to determine the prevalence and pattern of lipid abnormalities in Nigerians with types I and 2 DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
49
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 18 publications
9
49
0
Order By: Relevance
“…(19) This study was conducted in a hospital based population (Jabir Abu-Aliz Specialized center for diabetes) to assess the serum concentrations of lipoprotein (a) and lipid profile indexes as predictors for CAD in Sudanese insulin non-dependent diabetic patients compared with non-diabetic healthy subjects. Consistent with several reports from developing countries, (20)(21)(22)(23) Sudanese type 2 diabetics in this study showed dyslipidemia based on the NCEP-ATPIII guidelines which focuse on the role of the clinical approach to prevention of CHD.…”
Section: Discussionsupporting
confidence: 90%
“…(19) This study was conducted in a hospital based population (Jabir Abu-Aliz Specialized center for diabetes) to assess the serum concentrations of lipoprotein (a) and lipid profile indexes as predictors for CAD in Sudanese insulin non-dependent diabetic patients compared with non-diabetic healthy subjects. Consistent with several reports from developing countries, (20)(21)(22)(23) Sudanese type 2 diabetics in this study showed dyslipidemia based on the NCEP-ATPIII guidelines which focuse on the role of the clinical approach to prevention of CHD.…”
Section: Discussionsupporting
confidence: 90%
“…Comparable study also done by Mwita in Dar es Salaam in 2009, the prevalence of dyslipidemia among the diabetic patients was 88% [16]. Within the African continent, similar studies have revealed high prevalence of dyslipidemia among diabetic patients; in Nigeria 82.6% to 90.7% from 2008-2011 respectively [8,9,10] and in South Africa [11]. Other areas such as Tehran and USA, similarly high prevalence of dyslipidemia was also observed 88.9% and 97% respectively [17,18].…”
Section: Discussionmentioning
confidence: 48%
“…The prevalence of dyslipidemia is terrifyingly high within the African continent. The trend has been seen to increase, in Nigeria, the prevalence ranged from 82.6% to 90.7% from 2008 to 2011 respectively [8,9,10]. In South Africa the prevalence is over 90% [11].…”
Section: Introductionmentioning
confidence: 99%
“…26 The development of cardiovascular disease in diabetes mellitus is often predicted by several factors which include central obesity, hypertriglyceridemia, elevated low high density lipoprotein (HDL-C) levels, and hypertension. 27 In Ghana subjects with cardiovascular disease were older and had a higher incidence of hypertension 66% and nearly a quarter had diabetes. 28 Whereas, in Cameroon obesity 80%, hypertension 60%, hyperlipidaemia 43%, smoking 36%, and diabetes 26% were the major risk factors.…”
Section: Discussionmentioning
confidence: 99%